THE ECONOMIC AND FINANCIAL PERFORMANCE OF TOUR OPERATORS IN ITALY, FRANCE AND SPAIN: SOME COMPARATIVE EVIDENCE* - Migliaccio, Guido; Calvanese, Maria (Economy and Sociology, 2024)
Purpose. This article describes and evaluates the economic and financial dynamics of tour operators over the last decade in Italy, France and Spain, three European countries where tourism is relevant. Methodology. The balance sheets of a sample of 4,044 tour operators (1,043 Italian, 2,340 French, 661 Spanish) over the period between 2012 and 2021 were examined. The average trend of two indices is illustrated: the Return on Assets (ROA) and the Current Ratio. The data were subjected to extensive statistical processing. To compare differences between countries, Anova and, where necessary, Tukey-Kramer methods were used. Results. The lowest ROA values characterise Italy. In France and Spain, ROA has higher values with peaks, for Spain, of up to 10%. In 2020, it has negative values everywhere due to the pandemic. In 2021, on the other hand, it has positive values due to the general recovery of tourism. The nations have similar values. Other evidence is typical of the current report: France, in 2021, has an abnormal peak of 14%, after many stable years. Spain has shown a progressive increase in recent years. Italian values do not show any notable variations. The trends, which are globally similar in the three countries, are difficult to interpret and require further investigation. Implications. The survey enriches the modest international economic literature on tour operators. It is useful for those in the industry and for public authorities wishing to stimulate tourism.